2019
DOI: 10.1080/00220671.2019.1614514
|View full text |Cite
|
Sign up to set email alerts
|

Children encountering each other through storytelling: Promoting intercultural learning in schools

Abstract: Schools need concrete pedagogical tools to promote intercultural learning. The Storycrafting method is used to promote interactions between children that lead to a dynamic, rather than static, experience of culture. Children (aged 9-11) exchanged stories told using the Storycrafting method with another class in Finland, Scotland or an international school in Europe. To understand how children experience the intercultural encounters, the children's stories and other ethnographic materials are analyzed and frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 51 publications
0
19
0
4
Order By: Relevance
“…For such experiential or even transformative learning to take place, a disorienting dilemma (Senyshyn 2018), contradiction (Baraldi 2012), or out-of-comfort-zone experiences (Hyett et al 2019) are often necessary, while Martin and Griffiths (2014) stress the value of dialogue and critical reflection on those same experiences. The teachers' role (Piipponen and Karlsson 2019) and tension/discomfort balance (Grimminger-Seidensticker and Möhwald 2017;Mitchell and Paras 2018) are also reported as essential for successful intercultural learning.…”
Section: Main Methods Used Findings and Considerationsmentioning
confidence: 99%
“…For such experiential or even transformative learning to take place, a disorienting dilemma (Senyshyn 2018), contradiction (Baraldi 2012), or out-of-comfort-zone experiences (Hyett et al 2019) are often necessary, while Martin and Griffiths (2014) stress the value of dialogue and critical reflection on those same experiences. The teachers' role (Piipponen and Karlsson 2019) and tension/discomfort balance (Grimminger-Seidensticker and Möhwald 2017;Mitchell and Paras 2018) are also reported as essential for successful intercultural learning.…”
Section: Main Methods Used Findings and Considerationsmentioning
confidence: 99%
“…Understanding culture as a static, unchanging entity will likely lead to designing learning experiences that focus on concrete aspects, such as dress, food and festivals, which tend to reinforce cultural stereotypes and essentialism (Alvaré 2017;Piller 2017). However, if culture is understood as dynamic, layered and actively created by its members, there is more room for a nuanced understanding to develop (Dervin 2011;Layne, Trémion, and Dervin 2015;Piipponen and Karlsson 2019;Piller 2017).…”
Section: Knowledgementioning
confidence: 99%
“…There is evidence that international exchange projects which highlight cultural differences can unintentionally reinforce stereotypes and lead to a static view of culture (Gorski 2008;Lau 2015;MacKenzie, Enslin, and Hedge 2016;Royds 2015). To achieve the goal of reciprocal encountering, a story exchange project was developed through design-based research, where the focus shifted away from culture as a static entity to viewing culture dynamically as a process (Piipponen and Karlsson 2019). Three iterations took place so that the design and theory could be developed over time (Anderson and Shattuck 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Children also use the Storycrafting method to engage with power structures. Piipponen and Karlsson (2019) found that children participate in an intercultural Storycrafting exchange by narrating stories in a complex cultural web of connections, one which included their classmates, their teacher, and the partner class in another country. Story exchange promoted reciprocal intercultural encounters within and between the two groups of children, where the children find a way to connect as equals.…”
Section: The Studies Of Child Perspectives Open New Avenuesmentioning
confidence: 99%